alpha-Amylase immobilization on functionalized glass beads by covalent attachment - KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (ELSEVIER SCI LTD, 2007)
In this study alpha-amylase was covalently immobilized onto phthaloyl chloride-containing amino group functionalized glass beads. In this procedure. amide bonds were formed between amino groups on the protein and acid chloride groups on the glass surface. The surface modified beads were characterized using Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), energy dispersion spectrum (EDS) and UV-Vis spectroscopy. Immobilization was successfully performed under very mild conditions (15 degrees C. 4 h). The amount of covalently bound alpha-amylase was found 25.2 +/- 3.1 mg/g glass support. The optimum pH value for the free amylase was at pH 6.5. The optimum pH of the immobilized enzyme was shifted 1.0 pH unit to the acidic region. The immobilized alpha-amylase exhibited better thermostability than the free one. The free enzyme lost all its activity with in 15 days. Covalently bound amylase was stable up to 5 days and lost only 20% of activity in 25 days. The covalently bound enzyme demonstrated more than 98% activitv after 6 runs and 81.4% activity after 25 runs. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: covalent immobilization; alpha-amylase; enzyme; glass beads; EDS-SEM; THERMOSTABILITY; ENZYMES; SUPPORT; EPOXY; TOOL